2012
DOI: 10.1007/s00531-011-0736-1
|View full text |Cite
|
Sign up to set email alerts
|

Rock physics template (RPT) analysis of well logs and seismic data for lithology and fluid classification in Cambay Basin

Abstract: The Cambay Basin is 450-km-long north-southtrending graben with an average width of 50 km, having maximum depth of about 7 km. The origin of the Cambay and other Basins on the western margin of India are related to the break up of the Gondwana super-continent in the LateTriassic to Early-Jurassic (215 ma). The structural disposition of the Pre-Cambrian basement-a complex of igneous and metamorphic rocks exposed in the vicinity of the Cambay Basin-controls its architecture. The principal lineaments in the Basin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Based on these models, rock-physics templates (RPTs) can be used to estimate porosity and saturation (Liu et al, 2015;Pang et al, 2019Pang et al, , 2020. Studies showed that RPTs, built with acoustic impedance and P-to S-wave velocity ratio, serve as tools for lithology and fluid identification (Chi and Han, 2009;Datta Gupta et al, 2012;Ba et al, 2013). RPTs based on seismic attenuation also describe the effect of partial saturation, porosity, and permeability (Dvorkin and Mavko, 2006;Picotti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these models, rock-physics templates (RPTs) can be used to estimate porosity and saturation (Liu et al, 2015;Pang et al, 2019Pang et al, , 2020. Studies showed that RPTs, built with acoustic impedance and P-to S-wave velocity ratio, serve as tools for lithology and fluid identification (Chi and Han, 2009;Datta Gupta et al, 2012;Ba et al, 2013). RPTs based on seismic attenuation also describe the effect of partial saturation, porosity, and permeability (Dvorkin and Mavko, 2006;Picotti et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The workflow mentioned above (chart diagram) is showing one significant aspect for seismic inversion study. In this workflow, we could observe the presence of LFM and ULFM (Datta Gupta et al 2012).…”
Section: Fig 13mentioning
confidence: 99%
“…Michel [22] predicted porosity and oil saturation in shales, based on RPTs built with P-wave impedance (I P ) and the ratio between the P-and S-wave velocities (V P /V S ). Gupta et al [23] identified thin sandy layers saturated with oil, and Ba et al [24] estimated porosity and gas saturation. Carcione and Avseth [25] evaluated organic content, hydrocarbon saturation, and in-situ pressure in source rocks, and Liu et al [26] proposed a combination of fluid indicators.…”
Section: Introductionmentioning
confidence: 99%